Long duration single pulse intense pulsed light application in erythematotelangiectatic rosacea: An instrumental retrospective study - Pekmezci, Erkin (Annals of Medical Research, 2021)
Aim: Erythematotelangiectatic rosacea is a challenging condition due to poor therapeutic options. Treatment with intense pulsed light is partially effective after numerous sessions. Regarding the ‘thermal relaxation time’ principle and characteristic histopathology of erythematotelangiectatic rosacea, dilated capillaries and venules throughout the dermis, we proposed that directly targeting the largest vessels available by applying a long duration single pulse intense pulsed light mode, should decrease the mean number of treatment sessions to obtain a significant outcome. Material and Methods: Eighty seven erythematotelangiectatic rosacea patients who completed the proposed one month apart, four times consequtive intense pulsed light treatments with 25 ms pulse duration, single pulse and 10 J/cm2 fluence in the years of 2017-2019 were recruited retrospectively. Instrumental evaluations and self-assessment scorings were performed during the treatment period.Results: No adverse effect was recorded. Instrumentally evaluated results revealed a significant erythema quenching effect obtained at the end of 2nd treatment session (p=0.0011). Considering the decrease in erythema, both the instrumental and self-assessment values were found extremely significant after the 4th session, compared to initial values (p0.0001, for both).Conclusion: Considering the fast improvement recorded, intense pulsed light therapy with long pulse duration, single pulse, and low fluence may present a time saving and effective treatment option in erythematotelangiectatic rosacea patients with varied levels of severity. Also, the satisfactory outcome obtained by directly targeting the largest vessels available beginning from the initiation of therapy period, may be regarded as an indicator of the practicability of an identical mode of intense pulsed light treatment in diverse clinical presentations of erythematotelangiectatic rosacea.
Keywords: Erythema; fast improvement; rosacea; intense pulsed light